Analysis of node.js application performance using mongoDB drivers - Cayres, Leandro Ungari [UNESP] (2020)
At the last few years, the usage of NoSQL databases has increased, and consequently, the need for integrating with different programming languages. In that way, database drivers provide an API to perform database operations, which may impact on the performance of applications. In this article, we present a comparative study between two main drivers solutions to MongoDB in Node.js, through the evaluation of CRUD tests based on quantitative metrics (time execution, memory consumption, and CPU usage). Our results show which, under quantitative analysis, the MongoClient driver has presented a better performance than Mongoose driver in the considered scenarios, which may imply as the best alternative in the development of Node.js applications.